ANALISIS KEMAMPUAN DAN KEMAUAN DALAM MEMBAYAR TARIF PADA PENGGUNA JASA MODA TRANSPORTASI KAPAL LAUT (Rute Ternate-Sanana) - Dahlia Canra (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2022)
Sea transportation mode in this case ship is an alternative transportation mode that is most often chosen by the community when traveling on the Ternate - Sanana route. For this type of transportation mode, it is relatively smooth because almost every day it is available, there are 3 ships operating in one week. One important factor in the management of sea transportation services is fare. This is the reason people use this mode of transportation, because the fare is considered quite affordable. Therefore, this study was conducted to determine the Ability To Pay (ATP) and Willingness To Pay (WTP) users of the Ternate Sanana sea ship services, which can later be taken into consideration in evaluating the appropriate fare. From the data that has been processed, the Ability To Pay (ATP) value of Rp.471,722 and the Willingness to Pay (WTP) value of Rp.229,100. Keywords : Ability to Pay (ATP), Willingness To Pay (WTP), Fare, Sea Transportatio Mode, Ternate, Sanana.